Prognostic value of the full‐scale Periapical Index. (24th November 2014) - Kirkevang, L.‐L.; Ørstavik, D.; Wenzel, A.; Væth, M.
Abstract Aim To evaluate whether the full‐scale Periapical Index (PAI) can predict the periapical status over time in nonroot filled and root filled teeth. Methodology Full‐mouth radiographic surveys of a random sample from a general population were performed in 1997, 2003 and 2008. The present investigation included 330 persons who participated in all three examinations and 143 persons who participated in the first and second examination. At each examination, the presence or absence of a tooth and of a root filling was recorded, and a PAI score (1–5) was assigned to all teeth. Retreatment of a root filling was recorded for root filled teeth. Statistical analysis was carried out using ordinal logistic regression and logistic regression and computed as Wald's tests. Results At baseline, nonroot filled teeth had lower PAI scores than root filled teeth (P < 0.0001). A high baseline PAI increased the risk of extraction for both root filled (P < 0.001) and nonroot filled teeth (P < 0.001). At 5‐year follow‐up, PAI scores were higher when baseline PAI scores had been higher. The overall pattern for root filled and nonroot filled teeth was similar, however, the differences were statistically significant (P < 0.001). In particular, the follow‐up PAI score for nonroot filled teeth with baseline PAI score 1 or 2 was significantly lower than that of root filled teeth (P < 0.001). For root filled teeth with baseline PAI score 3, 4 or 5, the trend was reversed as they overall had slightly lower PAI scores at follow‐up (P = 0.023). Conclusion Repeated radiographic assessments of teeth using the full‐scale PAI reveal that each of the five scores had distinct prognostic value for the course of periapical disease over a 5‐year period for both nonroot filled and root filled teeth.